Factores que motivan a las y los jóvenes a participar del voluntariado Reinventando el Mundo – UNT, Trujillo 2018. - Diaz Canales, Elvia Milagros (2019)
The current descriptive research is aimed to investigate the factors that motivate the young people to participate in Volunteering Reinventing the World (Reinventando el Mundo) - UNT, in the year 2018. This research was conducted under a non-experimental design, whose sample population was constituted by 28 volunteers, whose ages range from 18 to 28 and who maintain an active participation and involvement within the voluntary service. The purpose of this study in the social reality is to publicize and identify part of those factors that encourage young people to be involved in voluntary work, by being part of a volunteer service and contributing to it with their work; being reflected in these factors those linked to personal, social and academic interests. This was measured, with the gathering of all the necessary information, which allowed establishing the existing relationship between the intervening variables by using the Deductive - inductive, descriptive, analytical, qualitative, ethnographic or phenomenological and statistical methods. As well as observation, interview, survey, focus group and bibliographic compilation techniques were used. Based on the following theoretical approaches; Human Scale Development Theory Approach, Human Rights Approach, Citizenship Approach, Sustainable Development Approach and Social Learning Approach. To better study of the information obtained in the results, the analysis and discussion were divided into two parts; the first part shows us the Sociocultural Characteristics of the sample population and the second part shows the division of the information obtained within the aspects denominated as social factors, academic - training and social factors.